2006
DOI: 10.1063/1.2202107
|View full text |Cite
|
Sign up to set email alerts
|

Centrosymmetric PbTe∕CdTe quantum dots coherently embedded by epitaxial precipitation

Abstract: A concept for the fabrication of highly symmetric quantum dots that are coherently embedded in a single crystalline matrix is demonstrated. In this approach, the formation of the quantum dots is induced by a transformation of an epitaxial 2D quantum well into an array of isolated precipitates with dimensions of about 25 nm. The formation process is driven by the immiscibility of the constituent materials resulting from their different lattice structures. The investigated PbTe/CdTe heterosystem combines two dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 22 publications
5
86
1
Order By: Relevance
“…Recently, it has been also demonstrated that similar PbTe/CdTe QDs can be synthesized by Pb + -implantation in CdTe and subsequent annealing [19], and by self-organization in-situ during epitaxial growth at the appropriated temperatures [20]. It has been demonstrated that PbTe/CdTe QDs are WLfree and can have highly centrosymmetric shapes (almost spherical) [2], they have atomically sharp interfaces [21] and they are strongly luminescent up to over 400K [20][21][22]. As the QD and host materials are almost lattice-matched (see Figure 4) a large number of layers separated by thin spacers can be grown.…”
Section: The Lead Salt Qd Materials Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been also demonstrated that similar PbTe/CdTe QDs can be synthesized by Pb + -implantation in CdTe and subsequent annealing [19], and by self-organization in-situ during epitaxial growth at the appropriated temperatures [20]. It has been demonstrated that PbTe/CdTe QDs are WLfree and can have highly centrosymmetric shapes (almost spherical) [2], they have atomically sharp interfaces [21] and they are strongly luminescent up to over 400K [20][21][22]. As the QD and host materials are almost lattice-matched (see Figure 4) a large number of layers separated by thin spacers can be grown.…”
Section: The Lead Salt Qd Materials Systemsmentioning
confidence: 99%
“…The QD material gap is not blueshifted (as a matter of fact, that would not be the case even under lattice mismatch, because lead salts have an anomalous behavior by which their gap decreases as pressure is applied [26]). Another consequence of the lack of strain is the possibility to grow small, centrosymmetric QDs (aspect ratio ~ 1) [2,[20][21][22]. On the other hand, lead salts have small effective masses for both electron and holes, and therefore, the number of confined levels is small for both kinds of carriers (they are direct gap semiconductors with almost symmetrical bands at the L point minimum).…”
Section: The Lead Salt Qd Materials Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium telluride (CdTe) thin films are widely used in photovoltaic (Colegrove et al, 2012) (McCandless and Sites 2003) (Okamoto, Yamada, & Konagai 2001) and other optoelectronic applications (Liang et al, 2012) (Brill et al, 2005) (Heiss et al, 2006) due to its low production cost, a desired direct band gap of ~1.5 eV, and an excellent absorption coefficient of 6 × 10 4 m -1 at 600 nm. A variety of methods have been applied to synthesize CdTe films such as molecular beam epitaxy (MBE) (Kim et al, 2004) (Han, Kang, & Kim 1999), physical vapour deposition (PVD) (Moutinho et al, 2008), high vacuum evaporation (HVE) (Terheggen et al, 2003), and close space sublimation (CSS) (Paudel, Xiao, & Yan 2014) .…”
Section: Introductionmentioning
confidence: 99%
“…A typical system is the rocksalt PbTe/zinc-blende CdTe heterostructure where a mild annealing of a PbTe quantum well, that is embedded in a CdTe matrix, results in the formation of PbTe quantum dots. 18 Since PbSe/CdSe heterostructures have similar crystallographic properties and several studies have shown the benefit of using PbSe/CdSe core-shell HNCs to enhance the stability and the tunability of the optical properties of PbSe nanocrystals, 19,20 we investigated PbSe/CdSe heteronanocrystals with UV photoelectron spectroscopy based on synchrotron radiation. In contrast to HNCs with similar lattice types, we observed a reproducible modification of the valence bands and core levels for the main elements in the HNCs as a function of the irradiation time.…”
Section: Introductionmentioning
confidence: 99%